PENGARUH UMUR HARAPAN HIDUP, RATA-RATA LAMA SEKOLAH, HARAPAN LAMA SEKOLAH, PENDAPATAN PER KAPITA DAN JUMLAH PENDUDUK TERHADAP GARIS KEMISKINAN DI KABUPATEN MINAHASA TENGGARA - Yemima Manengal; Vecky A.J. Masinambow; Krest D. Tolosang (PT. Hasba Edukasi Mandiri, 2025)
The poverty line is the minimum expenditure required by an individual to meet basic needs such as food, clothing, shelter, education, and healthcare. If a person’s expenditure falls below this threshold, they are categorized as poor. This study aims to analyze the influence of Life Expectancy, Average Years of Schooling, Expected Years of Schooling, Per Capita Income, and Population on the Poverty Line in Southeast Minahasa Regency. The analytical method used is multiple linear regression. The results show that Life Expectancy, Per Capita Income, and Population have a positive and significant effect on the Poverty Line. Meanwhile, Average Years of Schooling and Expected Years of Schooling have no significant effect on the Poverty Line in Southeast Minahasa Regency.